Sulphide and Dissolved Oxygen Concentrations in Batang Ai Hydroelectric Reservoir - Paka, Debbie Deborah; Ling, Teck Yee; Lee, Nyanti; Ismail, Norhadi; Emang, Justin Jok Jau (Universiti Malaysia Sarawak, 2013)
Anoxic condition of reservoir often results in the presence of sulphide in the water. Warm water column in Batang Ai Hydroelectric Dam is well-suited for the production of sulphide in the water column. Temperature, pH, dissolved oxygen (DO) and sulphide concentrations were measured at S locations at 3 different depths in the reservoir. Highest temperature recorded was 30.31 °c at STI while the lowest been recorded was 24.75 °C at ST4. The pH values were found to rang!; from 6.63 to 7.37. The sulphide levels were lower at the 1 m depth compared to 14 m and 27 m. They ranged from 0.3 to 6.7JlglL. Most of the stations (ST2, STI, ST4 and STS) were found to have higher concentration of sulphide at the 14 m compared to 27 m except at STI. Sulphide concentration was measured highest at 14 m of STS (14.7 IlgIL) and lowest at 1 m of ST2. The surface water concentration of sulphide at STI differ significantly with ST4 (p=0.024) while at both 14 m and 27 m depth, the concentrations of sulphide at STI were significantly. lower than STS. One way ANOV A shows that there were significant differences among stations at every depth (1m, p=O.028; 14 m,p=0.029; 27 m, p=O.028). Hence, the concentrations of sulphide were found to be different at every locations as well as different water column depending on the sampling sites.